Hukum Menyematkan Nama Suami Di Belakang Nama Istri (Studi Komparatif Lembaga Fatwa Lajnah Daimah Arab Saudi Dan Daarul Ifta’ Mesir) - Muhammad Taufiq Rajabbianur (Interdisciplinary Explorations in Research Journal, 2023)
Abstract Humans began to recognise names since the first man was created by God (Adam alaihi salam). This is explained by the books of the heavenly religions, which are the words of God that are believed to be true by human beings who believe in religion. There are many traditions of name usage in the world that are influenced by each culture that has a long history. Which each region has a different tradition of using names. One of the traditions that exist is the culture of adding the husband's name or the husband's family name behind the wife's name after marriage. The Fatwa of Lajnah Daimah Saudi Arabia and Daarul Ifta' Egypt are two institutions that have released fatwas regarding what is the law of Islam for a Muslim who adding the husband's name behind the wife's name as the culture of people in western countries. The type of research that will be used in this research is descriptive normative legal research through a comparative approach, which focuses on Islamic studies by examining the fatwas of the two institutions concerned, literature related to fiqh issues, as well as other supporting sciences such as history and sociology as tools and materials for analysis in this research. The results of the study found that the fatwa council of Lajnah Daimah Saudi Arabia ruled that it is forbidden to put the husband's name behind the wife's name because the mufti understands that putting the husband's name behind the wife's name is a form of associating oneself with the husband or the husband's family, and this is something that is prohibited and has a great threat. This is also considered as imitating the disbelievers (Tasyabuh bil kufr), which is obligatory for Muslims to be careful and leave such things. In contrast, the Fatwa Council of Daarul Ifta, Egypt, has ruled that it is permissible to add the husband's name after the wife's name because the mufti took into account the 'urf (customs) of the people in the country and was of the view that there is no woman in the practice, when she adopts her husband's name or surname, denies her parental relationship to her biological father. Such an act is merely a form of identification (Ta'rif) that the woman has married a man from a specific family. Keywords: Name, Adding, Attributing, ‘Urf, Lajnah Daimah, Daarul Ifta’ Abstrak Manusia mulai mengenal nama semenjak manusia pertama diciptakan oleh tuhan (Adam alaihi salam). Itulah yang dijelaskan oleh kitab – kitab agama samawi yang merupakan firman tuhan yang diyakini kebenarannya secara benar oleh golongan manusia yang beriman lagi beragama. Terdapat banyak tradisi penggunaan nama di dunia yang dipengaruhi oleh kebudayaan masing - masing yang memiliki sejarah yang panjang. Yang mana masing – masing daerah memiliki tradisi penggunaan nama yang berbeda. Salah satunya tradisi yang ada adalah kebudayaan menyematkan nama suami atau nama keluarga suami di belakang nama istri setelah menikah. Lembaga Fatwa Lajnah Daimah Arab Saudi dan Daarul Ifta’ Mesir merupakan dua lembaga fatwa yang telah mengeluarkan fatwanya terkait bagaimana hukum bagi seorang muslim yang menyematkan nama suami di belakang nama istri layaknya kebiasaan orang-orang di negeri barat. Jenis penelitian yang akan digunakan dalam penelitian ini adalah penelitian hukum normatif bersifat yang deskriptif melalui pendekatan komparatif, yang berfokus kepada kajian keislaman dengan mengkaji fatwa kedua lembaga yang bersangkutan, Literatur yang berkaitan dengan masalah fiqh, serta ilmu – ilmu penunjang lain seperti sejarah dan sosiologi sebagai alat dan bahan analisis dalam penelitian kali ini. Dari Hasil penelitian didapati bahwa lembaga fatwa Lajnah Daimah Arab Saudi memfatwakan haram menyematkan nama suami di belakang nama istri adalah karena mufti memahami bahwa menyematkan nama suami di belakang nama istri merupakan suatu bentuk penasaban diri kepada suami atau keluarga suami, dan ini merupakan suatu hal yang terlarang dan memiliki ancaman yang besar. Perkara ini juga dianggap sebagai meniru – niru orang kafir (Tasyabuh bil kufr) yang mana wajib bagi muslim untuk berhati hati dan meninggalkan perkara yang demikian itu. Berbeda dengan lembaga fatwa Daarul Ifta Mesir yang memfatwakan boleh menyematkan nama suami di belakang nama istri karena mufti mempertimbangkan ‘urf atau kebiasaan masyarakat di suatu negara dan berpandangan bahwa tidak ada satupun perempuan yang pada praktiknya ketika ia mengadopsi nama suami atau nama keluarga suaminya, ia menyangkal hubungan orang tua kepada ayah kandungnya. Perbuatan yang demikian itu hanya sebagai bentuk identifikasi bahwa perempuan tersebut telah menikah dengan seorang pria dari keluarga tertentu. Kata Kunci: Nama, Menyematkan, Menasabkan, Urf, Lajnah Daimah, Daarul ifta’